Integration of Science and Education, Innovation and Education-reform and Practice of "ASK" Special Talent Training Model for Cyberspace Security Major - Han, Bing; Ma, Bin; Li, Sa; Wang, Chunpeng (Journal of Educational Research and Policies, 2024)
In recent years, cyberspace security has become a key issue of national concern. At present, there is a shortage of high-quality professionals in cyberspace security. In view of the current education model, network security talents lack of innovation ability, practical ability is not strong, weak professional knowledge, and does not meet the requirements of safeguarding national network security and building a network power, this paper explores new ideas of network security talent training, and builds a new model of "ASK" characteristic network space security talent training based on the integration of science and education. With the integration of science and education as the main line, three characteristic talent training solutions (namely: Advisor, Speedy, Knowledge-graph) are proposed to ensure the quality of talents in cyberspace security.